Hostname: page-component-745bb68f8f-lrblm Total loading time: 0 Render date: 2025-02-11T11:05:11.060Z Has data issue: false hasContentIssue false

ON THE DIVISIBILITY OF SUMS INVOLVING APÉRY-LIKE POLYNOMIALS

Published online by Cambridge University Press:  14 March 2022

SHENG YANG
Affiliation:
Department of Mathematics, Wenzhou University, Wenzhou 325035, PR China e-mail: ysdj@sina.com
JI-CAI LIU*
Affiliation:
Department of Mathematics, Wenzhou University, Wenzhou 325035, PR China
Rights & Permissions [Opens in a new window]

Abstract

We prove a divisibility result on sums involving the Apéry-like polynomials

$$ \begin{align*} V_n(x)=\sum_{k=0}^n {n\choose k}{n+k\choose k}{x\choose k}{x+k\choose k}, \end{align*} $$

which confirms a conjectural congruence of Z.-H. Sun. Our proof relies on some combinatorial identities and transformation formulae.

Type
Research Article
Copyright
© The Author(s), 2022. Published by Cambridge University Press on behalf of Australian Mathematical Publishing Association Inc.

1 Introduction

In his ingenious proof of the irrationality of $\zeta (2)$ and $\zeta (3)$ , Apéry [Reference Apéry1] introduced the numbers

$$ \begin{align*} A_n=\sum_{k=0}^n{n\choose k}^2{n+k\choose k}^2\quad \text{and}\quad A_n'=\sum_{k=0}^n{n\choose k}^2{n+k\choose k}, \end{align*} $$

which are now known as the Apéry numbers. Since the appearance of the Apéry numbers, some interesting arithmetic properties have been gradually discovered. For instance, Sun [Reference Sun8, formula (1.6)] showed that for any prime $p\ge 5$ ,

$$ \begin{align*} \sum_{k=0}^{p-1}(2k+1)A_k\equiv p+\frac{7}{6}p^4B_{p-3}\pmod{p^5}, \end{align*} $$

where $B_n$ denotes the nth Bernoulli number. In 2012, Guo and Zeng [Reference Guo and Zeng3, Theorem 1.3] proved that

$$ \begin{align*} \sum_{k=0}^{p-1}(2k+1)^3A_k\equiv p^3\pmod{2p^6}. \end{align*} $$

In 2012, Sun [Reference Sun8] introduced the Apéry polynomials,

$$ \begin{align*} A_n(x)=\sum_{k=0}^n{n\choose k}^2{n+k\choose k}^2x^k, \end{align*} $$

and conjectured that

$$ \begin{align*} \sum_{k=0}^{n-1}\epsilon^k(2k+1)A_k(x)^m\equiv 0\pmod{n}, \end{align*} $$

where $\epsilon =\pm 1$ and $n,m$ are positive integers. This conjectural divisibility result was confirmed by Pan [Reference Pan5, Theorem 1.1].

In 2020, Sun [Reference Sun7, formula (1.8)] introduced the Apéry-like polynomials

$$ \begin{align*} V_n(x)=\sum_{k=0}^n {n\choose k}{n+k\choose k}{x\choose k}{x+k\choose k}. \end{align*} $$

Note that $V_n(n)=A_n$ and

$$ \begin{align*} V_n\bigg(-\frac{1}{2}\bigg)=\frac{1}{16^n}\sum_{k=0}^n{2k\choose k}^2{2n-2k\choose n-k}^2. \end{align*} $$

Let $p\ge 5$ be a prime and, for $x\in \mathbb {Z}_p$ , let $\langle x\rangle _p$ denote the least nonnegative integer a with $a\equiv x \pmod {p}$ . Sun [Reference Sun7, Theorem 4.5] also showed that for $x\not \equiv 0,-1\pmod {p}$ and $x'=(x-\langle x\rangle _p)/p$ ,

$$ \begin{align*} \sum_{k=0}^{p-1}(2k+1)V_k(x)\equiv p^3\frac{x'(x'+1)}{x(x+1)}+2p^4\frac{x'(x'+1)+1}{x(x+1)}H_{\langle x\rangle_p}\pmod{p^5}, \end{align*} $$

where $H_n=\sum _{i=1}^n1/i$ denotes the nth harmonic number.

Recently, Wang [Reference Wang10, Theorem 1.1] proved that for any prime $p\ge 5$ ,

$$ \begin{align*} \sum_{k=0}^{p-1}(-1)^k(2k+1)V_n\bigg(-\frac{1}{2}\bigg) &\equiv (-1)^{{(p-1)}/{2}}p+3p^3E_{p-3}\pmod{p^4},\\[10pt] \sum_{k=0}^{p-1}2^k(k+1)V_n\bigg(-\frac{1}{2}\bigg) &\equiv (-1)^{{(p-1)}/{2}}p+5p^3E_{p-3}\pmod{p^4}, \end{align*} $$

which confirm two supercongruence conjectures due to Sun [Reference Sun9, Conjecture 33].

In his talk at the 7th Chinese National Conference on Combinatorial Number Theory, Z.-H. Sun discussed the sums of squares of the Apéry-like polynomials $V_n(x)$ and proposed the following divisibility conjecture.

Conjecture 1.1. Let $p\ge 5$ be a prime. For $x\in \mathbb {Z}_p$ and $x\not \equiv -1/2\pmod {p}$ ,

$$ \begin{align*} \sum_{n=0}^{p-1}(2n+1)V_n(x)^2\equiv 0\pmod{p^2}. \end{align*} $$

The aim of this note is to give a positive answer to this problem as follows.

Theorem 1.2. Let $p\ge 5$ be a prime. For $x\in \mathbb {Z}_p$ ,

$$ \begin{align*} \sum_{n=0}^{p-1}(2n+1)V_n(x)^2\equiv \frac{p^2}{2\langle x\rangle_p+1}\pmod{p^2}. \end{align*} $$

2 Proof of Theorem 1.2

We begin with the following identity [Reference Guo2, formula (2.5)]:

(2.1) $$ \begin{align} {x\choose j}{x+j\choose j}{x\choose k}{x+k\choose k}=\sum_{s=0}^{j+k}{j+k\choose s}{s\choose j}{s\choose k}{x\choose s}{x+s\choose s}. \end{align} $$

Using (2.1) twice, we obtain

$$ \begin{align*} V_n(x)^2&=\sum_{j=0}^n\sum_{k=0}^n {n\choose j}{n+j\choose j}{n\choose k}{n+k\choose k}{x\choose j}{x+j\choose j}{x\choose k}{x+k\choose k}\\[2pt] &=\sum_{j=0}^n\sum_{k=0}^n \sum_{r=0}^{j+k}\sum_{s=0}^{j+k}{n\choose r}{n+r\choose r}{x\choose s}{x+s\choose s}{j+k\choose r}{r\choose j}{r\choose k}{j+k\choose s}{s\choose j}{s\choose k}. \end{align*} $$

It follows that

(2.2) $$ \begin{align} \sum_{n=0}^{p-1}(2n+1)V_n(x)^2 & =\sum_{j=0}^{p-1}\sum_{k=0}^{p-1} \sum_{r=0}^{j+k}\sum_{s=0}^{j+k}{x\choose s}{x+s\choose s}{j+k\choose r}{r\choose j}{r\choose k}{j+k\choose s}{s\choose j}{s\choose k} \notag\\[2pt] &\quad \times\sum_{n=0}^{p-1}(2n+1){n\choose r}{n+r\choose r}. \end{align} $$

Since

$$ \begin{align*} \sum_{n=0}^{N-1}(2n+1){n\choose r}{n+r\choose r} =\frac{N^2}{r+1}{N+r\choose r}{N-1\choose r}, \end{align*} $$

which can be easily proved by induction on N, we deduce that for $0\le r\le 2p-2$ ,

(2.3) $$ \begin{align} \sum_{n=0}^{p-1}(2n+1){n\choose r}{n+r\choose r} &=\frac{p^2}{r+1}{p+r\choose r}{p-1\choose r}\notag\\[2pt] &=\frac{p^2(p^2-1^2)\cdots(p^2-r^2)}{(r+1)r!^2}\notag\\[2pt] &\equiv \frac{(-1)^rp^2}{r+1}\pmod{p^2}. \end{align} $$

Substituting (2.3) into the right-hand side of (2.2) gives

(2.4) $$ \begin{align} \sum_{n=0}^{p-1}(2n+1)V_n(x)^2 &\equiv p^2\sum_{j=0}^{p-1}\sum_{k=0}^{p-1} \sum_{s=0}^{j+k}{x\choose s}{x+s\choose s}{j+k\choose s}{s\choose j}{s\choose k}\notag \\[2pt] &\quad \times\sum_{r=0}^{j+k}\frac{(-1)^r}{r+1}{j+k\choose r}{r\choose j}{r\choose k}\pmod{p^2}. \end{align} $$

Using the identity,

$$ \begin{align*} \sum_{r=0}^{j+k}\frac{(-1)^{r}}{r+1}{r\choose j}{j\choose r-k}=\frac{(-1)^{j+k}}{(j+k+1){j+k\choose j}}, \end{align*} $$

from [Reference Liu4, formula (2.2)], we get

(2.5) $$ \begin{align} \sum_{r=0}^{j+k}\frac{(-1)^r}{r+1}{j+k\choose r}{r\choose j}{r\choose k}={j+k\choose j}\sum_{r=0}^{j+k}\frac{(-1)^r}{r+1}{r\choose j}{j\choose r-k}=\frac{(-1)^{j+k}}{j+k+1}. \end{align} $$

Combining (2.4) and (2.5), we obtain

(2.6) $$ \begin{align} \sum_{n=0}^{p-1}(2n+1)V_n(x)^2 &\equiv p^2\sum_{j=0}^{p-1}\sum_{k=0}^{p-1} \sum_{s=0}^{j+k}\frac{(-1)^{j+k}}{j+k+1}{x\choose s}{x+s\choose s}{j+k\choose s}{s\choose j}{s\choose k}\pmod{p^2}\notag\\[2pt] &=p^2\sum_{s=0}^{2p-2}\sum_{j=0}^{p-1}\sum_{k=0}^{p-1} \frac{(-1)^{j+k}}{j+k+1}{x\choose s}{x+s\choose s}{j+k\choose s}{s\choose j}{s\choose k}. \end{align} $$

Since the summands on the right-hand side of (2.6) are congruent to $0$ modulo $p^2$ except for $j+k=p-1$ , we conclude that

$$ \begin{align*} \sum_{n=0}^{p-1}(2n+1)V_n(x)^2 &\equiv p\sum_{s=0}^{p-1}{x\choose s}{x+s\choose s}{p-1\choose s}\sum_{j+k=p-1}{s\choose j}{s\choose k}\pmod{p^2}\\[2pt] &=p\sum_{s=0}^{p-1}{x\choose s}{x+s\choose s}{p-1\choose s}{2s\choose p-1}, \end{align*} $$

where we have used the Chu–Vandermonde identity in the last step.

Furthermore, we have ${p-1\choose s}\equiv (-1)^s\pmod {p}$ and ${2s\choose p-1}\equiv p/(2s+1)\pmod {p}$ for $0\le s\le p-1$ . It follows that

(2.7) $$ \begin{align} \sum_{n=0}^{p-1}(2n+1)V_n(x)^2 &\equiv p^2\sum_{s=0}^{p-1}\frac{(-1)^s}{2s+1}{x\choose s}{x+s\choose s}\notag\\[2pt] &\equiv p^2\sum_{s=0}^{\langle x\rangle_p}\frac{(-1)^s}{2s+1}{\langle x\rangle_p\choose s}{\langle x\rangle_p+s\choose s}\pmod{p^2}. \end{align} $$

Next, we recall the identity [Reference Prodinger6, formula (2.1)],

(2.8) $$ \begin{align} \sum_{s=0}^n\frac{(-1)^s}{z+s}{n\choose s}{n+s\choose s}=\frac{(1-z)_n}{z(1+z)_n}. \end{align} $$

The case $z=1/2$ in (2.8) reads

(2.9) $$ \begin{align} \sum_{s=0}^n\frac{(-1)^s}{2s+1}{n\choose s}{n+s\choose s}=\frac{1}{2n+1}. \end{align} $$

Finally, combining (2.7) and (2.9), we obtain

$$ \begin{align*} \sum_{n=0}^{p-1}(2n+1)V_n(x)^2\equiv \frac{p^2}{2\langle x\rangle_p+1}\pmod{p^2}, \end{align*} $$

as desired.

Footnotes

The second author was supported by the National Natural Science Foundation of China (grant 12171370).

References

Apéry, R., ‘Irrationalité de $\zeta (2)$ et $\zeta (3)$ ’, Astérisque 61 (1979), 1113.Google Scholar
Guo, V. J. W., ‘Some congruences involving powers of Legendre polynomials’, Integral Transforms Spec. Funct. 26 (2015), 660666.CrossRefGoogle Scholar
Guo, V. J. W. and Zeng, J., ‘New congruences for sums involving Apéry numbers or central Delannoy numbers’, Int. J. Number Theory 8 (2012), 20032016.CrossRefGoogle Scholar
Liu, J.-C., ‘A generalized supercongruence of Kimoto and Wakayama’, J. Math. Anal. Appl. 467 (2018), 1525.CrossRefGoogle Scholar
Pan, H., ‘On divisibility of sums of Apéry polynomials’, J. Number Theory 143 (2014), 214223.CrossRefGoogle Scholar
Prodinger, H., ‘Human proofs of identities by Osburn and Schneider’, Integers 8 (2008), Article no. A10, 8 pages.Google Scholar
Sun, Z.-H., ‘Congruences for two types of Apéry-like sequences’, Preprint, 2020, arXiv:2005.02081.Google Scholar
Sun, Z.-W., ‘On sums of Apéry polynomials and related congruences’, J. Number Theory 132 (2012), 26732699.CrossRefGoogle Scholar
Sun, Z.-W., ‘Open conjectures on congruences’, Nanjing Univ. J. Math. Biquarterly 36 (2019), 199.Google Scholar
Wang, C., ‘On two conjectural supercongruences of Z.-W. Sun’, Ramanujan J. 56 (2021), 11111121.CrossRefGoogle Scholar